A-Bar Scrambling in Repetition in a Case of Mixed Transcortical Aphasia: Hints for the Psychological Reality of the Syntax/Pragmatic Interface - Ludovico Franco; Elisa Zampieri; Francesca Meneghello (Discours)
The present study deals with sentence repetition in MB, an Italian patient with mixed transcortical aphasia. In preliminary testing, MB spontaneously resisted accurate repetition when presented with sentences featuring morphosyntactic violations (see Davis et al., 1978). MB also managed to repeat all the proposed phrasal chunks, even in complex sentences. Interestingly, MB tended to move the constituents with the violation (always oblique arguments/adjuncts) to the beginning of the sentence or to another non-canonical position (e.g., dislocating adjuncts immediately before verbs). Thus, he selectively performed “adjunct scrambling”. A detailed experimental task confirmed that MB only moved adjuncts or optional complements. Interestingly, most of the scrambled constituents were prosodically-marked by pitch-peaks as contrastive foci. We argue that MB resorts to scrambling as a syntactic strategy. In doing so, he activates projections that encode information related to the interface between syntax and discourse-pragmatics.